2023
DOI: 10.14338/ijpt-22-00027.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 250 MeV Protons from the Varian ProBeam PBS System for FLASH Radiation Therapy

Abstract: Shoot-through proton FLASH radiation therapy has been proposed where the highest energy is extracted from a cyclotron to maximize the dose rate (DR). Although our proton pencil beam scanning system can deliver 250 MeV (the highest energy), this energy is not used clinically, and as such, 250 MeV has yet to be characterized during clinical commissioning. We aim to characterize the 250-MeV proton beam from the Varian ProBeam system for FLASH and assess the usability of the clinical monitoring ionization chamber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Figure 5b shows a magnified view of Figure 5a near the 15 Gy region, where the same plan delivered at the same requested nozzle beam current was repeated five times. The variation, calculated as the difference between maximum and minimum, was 0.34 Gy, which corresponds to 2.3%, consistent with the reported values 33,34 . As shown in Figure 5b, the five repetitions with different delivered doses can be well separated by the SICA detector signal, demonstrating the feasibility and suitability of using the SICA detector placed upstream as an in vivo dosimeter to estimate the dose delivered at the isocenter.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Figure 5b shows a magnified view of Figure 5a near the 15 Gy region, where the same plan delivered at the same requested nozzle beam current was repeated five times. The variation, calculated as the difference between maximum and minimum, was 0.34 Gy, which corresponds to 2.3%, consistent with the reported values 33,34 . As shown in Figure 5b, the five repetitions with different delivered doses can be well separated by the SICA detector signal, demonstrating the feasibility and suitability of using the SICA detector placed upstream as an in vivo dosimeter to estimate the dose delivered at the isocenter.…”
Section: Resultssupporting
confidence: 86%
“…An off‐the‐shelf brass aperture system was also presented to provide the desired dose profiles for small animal experiments. This experience can serve as a valuable reference for other centers interested in implementing FLASH radiotherapy preclinical research, especially those equipped with a similarly designed MIC, which suffers from saturation during FLASH delivery, including most ProBeam centers 13,33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, EBT‐XD films were used as dosimeters, also for UHDR irradiations at SCD C . Although there are not many dedicated studies about the response of EBT‐XD films in UHDR for photon beams, a dose overestimation of 3% – 5% for a dose rate of over 40 Gy/s was reported for protons 30–32 . The dose overestimation trends to increase with increasing dose rate, for instance, 12% overestimation was reported for dose rates of 7500 Gy/s 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there are not many dedicated studies about the response of EBT-XD films in UHDR for photon beams, a dose overestimation of 3% -5% for a dose rate of over 40 Gy/s was reported for protons. [30][31][32] The dose overestimation trends to increase with increasing dose rate, for instance, 12% overestimation was reported for dose rates of 7500 Gy/s. 30 Other studies have reported Abbreviations: ctc, center-to-center distance; FWHM, full width at half maximum; PVIR, peak-to-valley intensity ratio.…”
Section: Fwhmmentioning
confidence: 97%